On Some Key Principles Hydrological Simulation To Work With Geospatial Information - Костріков, C. В. (Man and Environment. Issues of Neoecology, 2014)
The paper represents the general concept of the watershed distributed models. Some fundamental peculiarities of the GIS-models for watershed hydrology have been discussed as well as key issues relevant to the distributed hydrological modeling done. In addition the geospatial data concept has been outlined in details, since this data accepted as the initial data sources for the GIS-modeling in the relevant domain. The paper has given some relevant examples from both well-known GIS, and author’s original software.